Объяснение:
а) х²-2x-15=0
(x²-2x+1)-1-15=0
(x-1)²-4²=0
(x-1-4)(x-1+4)=0
(x-5)(x+3)=0
x₁=5;x₂=-3
ответ:{-3;5}
б)x²+4x+3=0
(x²+4x+4)-4+3=0
(x+2)²-1²=0
(x+2-1)(x+2+1)=0
(x+1)(x+3)=0
x₁=-1;x₂=-3
ответ: {-3;-1}
в)2x²-16-18=0
2x²-34=0
2(x²-17)=0
x²=17
x₁=-√17; x₂=√17
ответ : {-√17;√17}
если в условии ошибка (пропущена переменная х)
2x²-16x-18=0
2(x²-8x-9)=0
x²-8x-9=0
(x²-8x+16)-16-9=0
(x-4)²-5²=0
(x-4-5)(x-4+5)=0
(x-9)(x+1)=0
x₁=9; x₂=-1
ответ: {-1;9}
г)3x²+18x+15=0
3(x²+6x+5)=0
x²+6x+5=0
(x²+6x+9)-9+5=0
(x+3)²-2²=0
(x+3-2)(x+3+2)=0
(x+1)(x+5)=0
x₁=-1; x₂=-5
ответ: {-5;-1}
Объяснение:
а) х²-2x-15=0
(x²-2x+1)-1-15=0
(x-1)²-4²=0
(x-1-4)(x-1+4)=0
(x-5)(x+3)=0
x₁=5;x₂=-3
ответ:{-3;5}
б)x²+4x+3=0
(x²+4x+4)-4+3=0
(x+2)²-1²=0
(x+2-1)(x+2+1)=0
(x+1)(x+3)=0
x₁=-1;x₂=-3
ответ: {-3;-1}
в)2x²-16-18=0
2x²-34=0
2(x²-17)=0
x²=17
x₁=-√17; x₂=√17
ответ : {-√17;√17}
если в условии ошибка (пропущена переменная х)
2x²-16x-18=0
2(x²-8x-9)=0
x²-8x-9=0
(x²-8x+16)-16-9=0
(x-4)²-5²=0
(x-4-5)(x-4+5)=0
(x-9)(x+1)=0
x₁=9; x₂=-1
ответ: {-1;9}
г)3x²+18x+15=0
3(x²+6x+5)=0
x²+6x+5=0
(x²+6x+9)-9+5=0
(x+3)²-2²=0
(x+3-2)(x+3+2)=0
(x+1)(x+5)=0
x₁=-1; x₂=-5
ответ: {-5;-1}
1) а4 - в4= 4(а-в)
2) а6 - в6= 6(а-в)
3) а8 - в8= 8(а-в)
4) а4 + а3 + а + 1= 4а+3а+а+1=8а+1
5) (а+в)3-(а-в)3=3а+3в-
-(3а-3в)=3а+3в-3а+3в=6в
6) (4а-4в)=4а+4в-
-(4а-4в)=4а+4в-4а+4в=8в